Colorful palate : a flavorful journey through a mixed American experience - Tawney, Raj (New York : Empire State Editions, an imprint of Fordham University Press, 2023)
"A timely self-examination of the "mixed" American experience featuring exclusive recipes and photographs from the author's multicultural family As citizens continue to evolve and diversify within the United States, the ingredients that comprise each flavorful household are waiting to be discovered and devoured. In Colorful Palate, author Raj Tawney shares his coming-of-age memoir as a young man born into an Indian, Puerto Rican, and Italian-American family, his struggles with understanding his own identity, and the mouthwatering flavors of the melting pot from within his own childhood kitchen. While the world outside can be cruel and unforgiving, it's even more complicated for a mixed-race kid, unsure of his place in the world. Turning to his mother and grandmother for guidance, Tawney's assistance in the kitchen provided intimate moments and candor as he listened to the tales behind each culinary delicacy and the women who perfected them. Each lovingly prepared meal offered another opportunity to learn more about his extraordinary heritage. The ability to create delicious fare with his family wasn't just a duty for the grand ladies who raised him; they were a survival tactic for navigating new and unknown cultures, not always willing to accept them at first or even a hundredth glance. As Tawney examines both himself and his loved ones through the formative stages of his life, from boyhood through adulthood, he begins to realize, through all of the chaos and confusion, just how "American" he actually was. In this contemporary coming-of-age tale, Tawney tackles personal hot-button issues about race and identity through poignant, heartfelt moments centered around delicious meals. From succulent tandoori chicken to delectable arroz con habichuelas to scrumptious spaghetti and meatballs, Tawney shares his family recipes along with the intimate stories he overheard in the kitchen as he played sous chef to hundreds of recipes that not only span continents but come with their own personal histories attached. Colorful Palate is a tale of the mixed experience, one of the millions that rarely gets told, undefined by a single group or birthright, and unapologetic about its lack of classification"--
Frontmatter -- PROLOGUE -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Acknowledgments -- About the Author
Raj Tawney is a writer and journalist whose work largely reflects his New York-area upbringing and sensibility. Raised in an Indian, Puerto Rican, and Italian-American household, Tawney has explored his own race and identity through stories published in The New York Times, The Washington Post, NBC News, USA Today, Smithsonian magazine, and many other outlets throughout the country.
Print version record.
JSTOR
Keywords: Multiculturalism -- United States; Multiracial people -- United States; Cooking -- United States; Cultural pluralism -- United States; Multiculturalisme -- États-Unis.; Diversité culturelle -- États-Unis.; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; Cooking; Cultural pluralism; Multiculturalism; Multiracial people; United States